2021
DOI: 10.1093/isagsq/ksab024
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Exceptionalism: Securitization and COVID-19

Abstract: The suggestion that we “are at war” with the coronavirus pandemic was not uncommon in national representations of the challenge posed by the virus. Such a representation was in turn frequently linked to the imperative of emergency responses, including expanded police powers, national lockdowns, and border closures. For theorists of securitization, this is not surprising. For them, the language of security and existential threat enables extraordinary and exceptional practices. This paper interrogates these assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 75 publications
(51 reference statements)
0
20
0
Order By: Relevance
“…Triggered in situations of extreme risk to public safety, infrastructure or security, the special powers exercised under emergency legislation grant public officials temporary authority to issue directives that go beyond standard norms and avoid parliamentary scrutiny. For this reason, emergency laws are highly contested and often viewed as undemocratic (Kirk & McDonald, 2021 ). This was particularly so in Belgium, which goes against its principle of a non-hierarchical dual federalism where powers are exclusively allocated to communities, regions or the federal state (Bursens, 2020 ; Bursens et al, 2022 ; Peeters, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Triggered in situations of extreme risk to public safety, infrastructure or security, the special powers exercised under emergency legislation grant public officials temporary authority to issue directives that go beyond standard norms and avoid parliamentary scrutiny. For this reason, emergency laws are highly contested and often viewed as undemocratic (Kirk & McDonald, 2021 ). This was particularly so in Belgium, which goes against its principle of a non-hierarchical dual federalism where powers are exclusively allocated to communities, regions or the federal state (Bursens, 2020 ; Bursens et al, 2022 ; Peeters, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Scholars and analysts have identified numerous pronounced uses of securitization in the way COVID-19 has been talked about by medical professionals, political leaders, and media commentators, among other relevant speakers with a public platform (e.g., Al-Sharafat, 2020;Dimari & Papadakis, 2022;Kirk & McDonald, 2021;Krasna, 2020;Rogers, 2020;Vivek, 2020). Many of these analytical accounts highlight the problematic aspects of securitized framing (e.g., Grančayová, 2021;Rogers, 2020).…”
Section: літератураmentioning
confidence: 99%
“…An effort which led to growing National distrust on its institutions as well as the severely low vaccination rate of 18% as of August 2021 (Stronski & Kier, 2021). To further add to this, a recent study on how the UK, Australia and New-Zealand structured their responses to the COVID-19 outbreak found that these countries mostly trusted in their Institutional structure to hamper the spread of the contagion (Kirk & McDonald, 2021). UN data on 28 countries suggests that after an initial trend of positive growth in Institutional Trust during the first half of 2020, we are now seeing an inversion of that trend back to pre-pandemic levels (UN, 2021).…”
Section: Institutional Exceptionalismmentioning
confidence: 99%